Controversial Criminal Punishment for Victim of the Spread of Immoral Chat - Rachmadan Eka Cipta; Ali Masyhar (Universitas Negeri Semarang, 2021)
The purpose of this research is to (1) analyze the Supreme Court's consideration of victims of the spread of sordid chatter in the Supreme Court's decision Number 574K / PID.SUS / 2018, and (2) analyze the arguments of the Public Prosecutor regarding the offense Article 27 paragraph (1) juncto Article 45 paragraph (1) of the Information and Electronic Transaction Law in decision No. 574K / PID.SUS / 2018. This type of research uses qualitative methods with a normative juridical approach. In this method, secondary data uses the decision of the Mataram District Court Number: 265 / Pid.Sus / 2017 / PN.MTR and the decision of the Supreme Court Number 574 K / Pid.Sus / 2018. Primary data to support this research were obtained from interviews of the Supreme Court of the Republic of Indonesia and the Institute for Criminal Justie Reform. Results and discussion of research (1) The values ​​underlying the Supreme Court in the Supreme Court's decision Number 574K / PID.SUS / 2018 and (2) the Prosecutor's argument The Public Prosecutor related to offense Article 27 paragraph (1) jo Article 45 paragraph (1) of the Information and Electronic Transaction Law in the decision No. 574K / PID.SUS / 2018. Overall it can be concluded that (1) The value underlying the Supreme Court in passing this decision is that the judge tries to apply the benefits of the law. (2) The Public Prosecutor's Arguments in indicting or in prosecution cannot describe the offenses that are charged to the defendant, this is a serious record in the first-level court of the indictment and the demands of the Public Prosecutor are declared unproven on the defendant.